Effect of genotype on chemical composition and fatty acid profile of guinea pig carcass (Cavia porcellus L.) - Hidalgo Lozano, Víctor (2023)
The aim of this study was to evaluate the effect of the genotype on the deposition curve of the chemical components and fatty acid profile of carcass of guinea pigs of Peru and Cieneguilla genotypes. Forty-eight male guinea pigs (24 per genotype), randomly distributed in pens with three animals each per genotype were used. Management and feeding protocols, up to 32 wk of age, were similar for both genotypes. The deposition curve of the chemical components was determined using the Gompertz equation. Data of the fatty acid profile were submitted to analysis of varianza under a Randomized Complete Block Design using the SAS Studio Environment software, with a significance level of α = 0.05. The results showed that the asymptote of the moisture and protein content in the carcass of the Peru genotype was higher (P < 0.05) than that of Cieneguilla genotype, but not in the fat content, which was similar (P > 0.05) in both genotypes.  Likewise, the function of the relationship between the maximum deposition rate of the three chemical components and the content at adulthood (k) was similar (P > 0.05) in the two genotypes. The age of maximum moisture deposition rate and total protein at the inflection point (ti) are lower than the maximum fat deposition rate in both genotypes. Regarding the fatty acid profile of the carcass, the content of total and individual saturated fatty acids was similar (p > 0.05) in the two genotypes was observed. However, the content of total monounsaturated fatty acids and oleic acid (C18:1C) were higher (p < 0.05) in the Cieneguilla genotype, while the content of total polyunsaturated fatty acids, linoleic and linolenic acids were higher (P < 0.05) in the carcass of guinea pigs of the Peru genotype. In conclusion, the asymptote of moisture content and crude protein in adulthood was higher (p < 0.05) in the Peru genotype. In saturated fatty acid content, there were no statistical differences between both genotypes, but the Cieneguilla genotype contains a higher (p < 0.05) percentage of monounsaturated fatty acids and the Peru genotype has a higher (p < 0.05) percentage of polyunsaturated fatty acids.